2013
DOI: 10.1016/j.jaip.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Mechanisms of Environmental Tobacco Smoke in Children with Poorly Controlled Asthma: Results from a Multicenter Clinical Trial

Abstract: Background Environmental tobacco smoke (ETS) negatively affects children with asthma. The prevalence of ETS exposure among children with poor asthma control may be changing. Importantly, the mechanisms by which ETS worsens asthma control are poorly understood. Objective We describe how ETS affects gastroesophageal reflux (GER), respiratory infections, and leukotriene production among children with poor asthma control. Methods We analyzed data from 306 children between 6 and 17 years of age with poorly cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…10, 21-23 Indoor SHS exposure, particularly maternal smoking, was associated with a 52% increased risk of wheeze and 20% increased risk of asthma at age 5-18 years, 24 and any home SHS exposure was associated with increased asthma symptoms. 25 Identifying factors associated with frequent SABA medication use, indicative of poor asthma control, including allergen sensitization and indoor exposures to allergens and SHS may be helpful in targeting individualized environmental control as well as community level asthma interventions for inner-city families. Therefore, the objective of this study was to examine factors, including allergic sensitization and second hand smoke (SHS) exposure, associated with high SABA use among low-income inner-city children with frequent ED visits for asthma.…”
Section: Introductionmentioning
confidence: 99%
“…10, 21-23 Indoor SHS exposure, particularly maternal smoking, was associated with a 52% increased risk of wheeze and 20% increased risk of asthma at age 5-18 years, 24 and any home SHS exposure was associated with increased asthma symptoms. 25 Identifying factors associated with frequent SABA medication use, indicative of poor asthma control, including allergen sensitization and indoor exposures to allergens and SHS may be helpful in targeting individualized environmental control as well as community level asthma interventions for inner-city families. Therefore, the objective of this study was to examine factors, including allergic sensitization and second hand smoke (SHS) exposure, associated with high SABA use among low-income inner-city children with frequent ED visits for asthma.…”
Section: Introductionmentioning
confidence: 99%
“…58 Urinary LTE4 concentrations also have been associated with acute exacerbations of asthma 59 and the degree of airflow limitation, 57 but some confounding of the biomarker might exist. Recent studies have suggested that LTE4 concentrations are increased in response to environmental tobacco smoke exposure 60 ; however, increased LTE4 concentrations are still predictive of future exacerbations in children with asthma exposed to secondhand smoke. 61 Other prospective clinical trials in which urinary LTE4 was assessed as a biomarker remain promising.…”
Section: Leukotriene Ementioning
confidence: 99%
“…In addition, other genes with potential interactions with tobacco smoking and risk for asthma exacerbations have been identified in candidate gene linkage approaches [19][20][21][22].…”
Section: Genetic Mechanismsmentioning
confidence: 99%